The future of pensions and healthcare in a rapidly ageing world. Scenarios to 2030 - Sikken, Bernd Jan; Davis, Nicholas; Hayashi, Chiemi; Olkkonen, Heli (Geneva, 2008)
"The World Economic Forum’s report The Future of Pensions and Healthcare in a Rapidly Ageing World – Scenarios to 2030, indicates that new forms of collaboration between key stakeholders – individuals, financial institutions, healthcare providers, employers, and governments - will be critical to finance the ongoing well-being of current and future generations in a sustainable manner."